Peningkatan Rasa Percaya Diri Anak Yatim dan Dhuafa melalui Bimbingan Konseling Islam - Iim Fatimah; Ucin Muksin (Department of Islamic Guidance and Counseling, Faculty of Dakwah and Communication, UIN Sunan Gunung Djati Bandung, 2017)
This study aims to: 1) To know the program of counseling guidance of Islam in the foundation of orphans and dhuafa al-Kasyaf; 2) To know the implementation of counseling guidance of Islam in Yayasan orphan and dhuafa al-Kasyaf; 3) To know the results of counseling guidance of Islam efforts to increase the confidence of orphans and poor people in the Foundation al-Kasyaf. This research method uses qualitative research approach descriptive method research type of job analysis and activity. Descriptive method is a method in researching the status of human groups, an object, a condition condition, a system of thought or a class of events in the present. Based on the research, Based on the results of the research that, children carry out guidance with the board that is in the foundation, they do lectures or tausyah practice in front of his friends and administrators. Based on intrinsic motivation (from within), and extrinsic motivation (from outside). Evidently, the child can be involved in the guidance activity, this is in accordance with the results of the questionnaire to the children, showing that the confidence of children while doing the exercises looks very good and also seen when they greet the guests who come and look when they have free time to fill their spare time with positive activities, such as cleaning up the environment, reading books, or other activities. Penelitian ini bertujuan untuk: 1) Untuk mengetahui program bimbingan konseling islam di yayasan yatim dan dhuafa al-Kasyaf; 2) Untuk mengetahui pelaksanaan bimbingan konseling islam di Yayasan yatim dan dhuafa al-Kasyaf; 3) Untuk mengetahui hasil bimbingan konseling islam upaya meningkatkan rasa percaya diri anak yatim dan dhuafa di Yayasan al-Kasyaf. Metode Penelitian ini menggunakan pendekatan kualitatif penelitian metode deskriptif jenis penelitian analisa pekerjaan dan aktivitas. Metode deskriptif adalah suatu metode dalam meneliti status kelompok manusia, suatu objek, suatu situasi kondisi, suatu sistem pemikiran ataupun suatu kelas peristiwa pada masa sekarang. Berdasarkan penelitian, Berdasarkan hasil dari penelitian bahwasanya, anak melaksanakan bimbingan dengan pengurus yang ada di yayasan, mereka melakukan latihan ceramah atau tausyah dihadapan teman-temannya dan pengurus. Berdasarkan motivasi intrinsik (dari dalam), dan motivasi ekstrinsik (dari luar). Terbukti, anak dapat terlibat dalam kegiatan bimbingan, hal ini sesuai dengan hasil penyebaran angket kepada anak, menunjukan bahwa rasa percaya diri anak saat melakukan latihan terlihat sangat bagus dan juga terlihat ketika mereka menyapa tamu yang datang dan terlihat ketika mempunyai waktu senggang mereka mengisi waktu luang tersebut dengan kegiatan yang positif, seperti bersih-bersih lingkungan sekitar, membaca buku, ataupun kegiatan lainnya.